2006
DOI: 10.1111/j.1740-0929.2006.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in walking parameters of milking cows after hoof trimming

Abstract: We examined the walking parameters of milking cows in relation to hoof trimming. The hooves of eight Holstein cows were trimmed. Two days before and after the hoof trimming, walking behavior, limb angles, back posture and vertical movement of the back while walking were measured. Walking rate (1.27 vs 0.87 m/s; P = 0.003), step length (1.46 vs 1.33 m; P = 0.009) and stepping rate (0.78 vs 0.65 steps/s; P = 0.046) were found to increase significantly after hoof trimming. Limb angles at the start and end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…Carvalho et al (2007) reported that trimmed cows had a more confident and stable walk. This was confirmed by Aoki et al (2006) who quantitatively indicated that walking characteristics improved after trimming by increasing walking rate, step length and stepping rate. Limb angles also showed less 'on tiptoe' locomotion after trimming.…”
Section: Introductionsupporting
confidence: 64%
“…Carvalho et al (2007) reported that trimmed cows had a more confident and stable walk. This was confirmed by Aoki et al (2006) who quantitatively indicated that walking characteristics improved after trimming by increasing walking rate, step length and stepping rate. Limb angles also showed less 'on tiptoe' locomotion after trimming.…”
Section: Introductionsupporting
confidence: 64%
“…yellow circles) attached to hooves, limb joints, withers, or back-line contour. Video recordings of cows walking with markers are later analysed with software for kinematic variables (Flower et al, 2005;Aoki et al, 2006;Blackie et al, 2013). Another technique uses image preprocessing, in which video recordings are transformed into sequences of binary images to facilitate the detection of anatomical parts of cows (Song et al, 2008;Van Hertem et al, A c c e p t e d M a n u s c r i p t 2013; Viazzi et al, 2013).…”
Section: Automatic Locomotion Scoring Systemsmentioning
confidence: 99%
“…Walking rate, step length and stepping rate were measured in accordance with protocols previously described (Aoki et al . ). Briefly, digital camcorder still pictures were captured consecutively on a personal computer by using freely available software (Area61 Video browser), and the three kinematic measures were calculated by using image analysis software (Adobe Photoshop CS4 Extended, Adobe Systems, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…; Telezhenko & Bergsten ; Aoki et al . ), the ‘support phase’ was defined as the period between when each hoof touched the floor (hoof strike) and when it lifted off the floor (hoof off). The difference in hoof positions between the start of the first support phase of one forelimb and the start of the last support phase of one forelimb (regardless of the limb side) was regarded as the walking distance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation